Morpho-facial variations in physical features of two tribal populations of Kargil (Ladakh, India): A bio-anthropological investigation - Sehrawat, Jagmahender Singh; Ali, Mohd (Anthropological Review, 2023)
Somatoscopy is a systematic and cumulative visual examination of the morphological features of an individual. Physical anthropologists have classified humans into certain specific groups on the basis of specific morphoscopical features, and such variations have been widely studied. Fourteen somatoscopic traits of 800 adult (>25years) Ladakhi individuals, belonging to two Kargil (India) tribal groups (Brokpas and Purigpas) were examined; four hundred (N=400) healthy individuals from each tribe i.e., 221 males and 179 females of the Brokpa tribe and 210 males and 190 females of the Purigpa tribe, comprised the present study sample. Statistically significant differences were noticed between the Brokpas and the Purigpas with respect to the frequencies distribution of their skin colour, hair form, facial contour/ profile, nasal types and presence/absence of epicanthic fold, prognathism, Darwin’s tubercle, Adam’s apple, scaphoid, attached ear lobe etc. The Brokpas exhibited significant sex differences in skin colour, eye colour, hair form, nasal septum, nasal tip, epicanthic fold, ear lobe, and Adam apple, whereas only skin colour, eye colour, ear lobe attachment, hair form, and prognathism were found significantly different in the two sexes of Purigpas. The morphological variation and sexual dimorphism in the human physical features of the two Ladakhi tribes will add to the existing knowledge regarding the anthropological characteristics of different ethnic groups of India. The differences in their morphological traits may be due to the differences in their genetic adaptations as the two tribal groups originated from two different ancient populations i.e., the Brokpas are of the European origin and the Purigpas are the descendants of the Tibeto-Mongoloids. The results of this study, however, need to be supplemented with a compressive investigation to confirm the heterogeneity in the morphological and genetic features of the two tribal groups of Ladakh (India) and the influence of differential ancestral migrations on the facial features of the individuals of the two tribal groups.